Adolescences experience of gender-based violence: a qualitative study - Rr Dian Tristiana; Ika Nur Pratiwi; Dianis Wulan Sari; Ah Yusuf; R Endro Sulistyono (International Journal of Public Health Science (IJPHS), 2023)
Violence towards women is a serious global problem which can affect mental, physical, sexual dan reproductive health. This study aimed to explore adolescents’ experiences of gender-based violence. This study used a qualitative phenomenology design to assess the adolescent’s experience of gender-based violence. The participants were 15 female adolescents aged 15-18. Participants were interviewed using semi-structured in-depth interviews. The qualitative data obtained were transcribed and analyzed using the Colaizzi approach. The results were structured into four themes according to the adolescent experiences of violence. The themes were the violence experienced; Victim’s efforts to deal with the violent incident; Barriers to not reporting or telling others; hope and desire for violence prevention. This study highlights that almost the majority of female adolescent was disclosed to tell other people about incidents of violence. Adolescents tend to feel self-blame and consider that the violent behavior happened because of their fault. This finding emphasized the intervention to resolved the unmet need to facilitate reporting of gender-based violence by victimized adolescents. The interventions must address the stigma, increase community understanding about taboos, and promote gender-based violence education at the school, family, and societal levels.